Rheological properties, emulsion and oxidative stability of cocoa butter based salad dressing during storage - Ishak, Izzreen; Hussain, N.; Mohd Hariri, N. A. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
This study was carried out to determine the rheological property, emulsion stability, optimal microscope observation and oxidative stability of the newly formulated cocoa butter salad dressing (CBSD) and its storage study at 18 °C for 28 days. The most stable ratio 20 % CBSD was selected for the storage study due to insignificantly (p>0.05) similar rheological characteristics with control in terms of flow behavior (0.35±0.00), consistency index (18.78±0.20), apparent viscosity (3.48±0.02) and emulsion stability (97.9±0.96). The optical observation showed that the droplet size of 20% CBSD was similar to the control and commercial salad dressing. The iodine and peroxide value also increased throughout shelf life period comparable to commercial salad dressing. This research may benefit the cocoa industry to meet the consumer’s demand for values add food products.